Dynamics of fine grinding in a fluidized bed opposed jet mill - Köninger, Benedikt; Hensler, Timo; Romeis, Stefan; Peukert, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
Keywords: Fine dry comminution; First order kinetics; Fluidized bed opposed jet mill; Process dynamics

High-density risers as reactor system for benzene synthesis by non-oxidative dehydroaromatization of methane - fluid-dynamic investigations - Hensler, Timo; Zhang, Yingxue; Mleczko, Leslaw; Assmann, Jens; Bellinghausen, Rainer; Schwieger, Wilhelm; Wirth, Karl-Ernst (11th International Conference on Fluidized Bed Technology, CFB 2014, 2014)
As a precursor for synthesis of dyes, polymers, fuel additives and various solvents benzene has become an indispensable base chemical in a large field of industrial processes. To date the industrial benzene demand is covered in large part by benzene which is extracted from crude oil. However, scarcity of oil resources accompanied by increasing prices for oil derived chemicals necessitates the development of alternative processes to satisfy the market's benzene demand. The presented work deals with the development of a reactor model for benzene synthesis by non-oxidative dehydroaromatization of methane. Based on model calculations a riser reactor operated at high solids concentrations has been found to allow for most efficient operation. Together with the model experimental data are presented in order to evaluate the fluid-dynamic feasibility of the suggested flow condition within a pilot plant scale circulating fluidized bed. Experimental data show that stable operation can be achieved at cross-section averaged solids concentrations up to 30 vol.%.

Horizontal secondary gas injection in fluidized beds: Solid concentration and velocity in multiphase jets - Köninger, Benedikt; Hensler, Timo; Schug, Sebastian; Arlt, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2017)

Non-invasive investigation of the cross-sectional solids distribution in CFB risers by X-ray computed tomography - Hensler, Timo; Firsching, Markus; Gomez Bonilla, Juan Sebastian; Woerlein, Thorsten; Uhlmann, Norman; Wirth, Karl-Ernst (Powder Technology, 2016)
We apply X-ray computed tomography for non-invasive investigation of the distribution of solids over the cross-section of a pilot plant scale circulating fluidized bed riser and present a novel method to derive volumetric solids concentrations from tomographic raw data. In this, the elimination of low-energetic radiation from the incident X-ray spectrum plays an essential role to avoid detrimental beam hardening effects, which are caused by the pipe material and the fluidized solids. The presented technique is applied for quantitative analysis of the radial solids concentration distribution in a gas-solid circulating fluidized bed riser. The examined operating range covers mean solids concentrations between 2.7 vol% and 37.2 vol% whilst the superficial gas velocity is varied between 1.5 m s-1 and 6.0 m s-1. The high spatial resolution of the measured data permits evaluation of the influence of the overall solids holdup and the superficial gas velocity on the radial solids concentration profile. Comparison of the cross-section averaged solids concentrations obtained by X-ray computed tomography with those inferred from differential pressure measurements confirms the high accuracy of the applied method. Based on a comprehensive set of measurement data a model is developed that allows for the prediction of the radial solids concentration distribution in vertical gas-solid upflow.
EAM Import::2019-03-08

Particle tracking in fluidized beds with secondary gas injection - Hensler, Timo; Tupy, Martin; Strer, Timo; Pöschel, Thorsten; Wirth, Karl-Ernst (7th World Congress on Particle Technology, WCPT 2014, 2015)
Fluidized beds with secondary gas injection enjoy great popularity in process industry. Owing to their characteristic properties such as intense mixing of solids, excellent mass and heat transfer conditions as well as easy handling of solids, this type of apparatus is applied in various fields of process engineering nowadays. In the past decades research concerning fluidized beds with secondary gas injection has focused on understanding how solid particles and the injected gas are distributed within the apparatus. With the aid of invasive measurement techniques the region surrounding the injector nozzle was investigated with respect to the penetration depth of the gas jet above the nozzle orifice as well as the jet opening angle. A major drawback of the previously used measurement techniques consists in their invasive nature. Penetration of the injection zone by a probe can severely influence the local flow pattern and consequently has a detrimental effect on the reliability of the measured data. Therefore in the presented work for the first time the solids distribution as well as the motion of a single particle in a fluidized bed with secondary gas injection has been investigated by positron emission particle tracking (PEPT). This non-invasive technique is based on labeling one single particle, randomly selected from the bulk, radioactively, which allows for tracking its motion with high temporal and spatial resolution. The obtained data are compared with results derived from invasive measurements. Moreover PEPT-data have been used to perform investigations on the residence time behavior of particles within the jet region and the suspended phase. It could be found that the combination of invasive measurements and PEPT provide valuable information for the design and optimization of fluidized bed reactors with a well-defined injection zone.
Keywords: Fluidized bed; positron emission particle tracking; residence time behavior; secondary gas injection; solids distribution

Particle Tracking in Fluidized Beds with Secondary Gas Injection - Hensler, Timo; Tupy, Martin; Strer, Timo; Pöschel, Thorsten; Wirth, Karl-Ernst (Procedia Engineering, 2015)
Fluidized beds with secondary gas injection enjoy great popularity in process industry. Owing to their characteristic properties such as intense mixing of solids, excellent mass and heat transfer conditions as well as easy handling of solids, this type of apparatus is applied in various fields of process engineering nowadays. In the past decades research concerning fluidized beds with secondary gas injection has focused on understanding how solid particles and the injected gas are distributed within the apparatus. With the aid of invasive measurement techniques the region surrounding the injector nozzle was investigated with respect to the penetration depth of the gas jet above the nozzle orifice as well as the jet opening angle. A major drawback of the previously used measurement techniques consists in their invasive nature. Penetration of the injection zone by a probe can severely influence the local flow pattern and consequently has a detrimental effect on the reliability of the measured data. Therefore in the presented work for the first time the solids distribution as well as the motion of a single particle in a fluidized bed with secondary gas injection has been investigated by positron emission particle tracking (PEPT). This non-invasive technique is based on labeling one single particle, randomly selected from the bulk, radioactively, which allows for tracking its motion with high temporal and spatial resolution. The obtained data are compared with results derived from invasive measurements. Moreover PEPT-data have been used to perform investigations on the residence time behavior of particles within the jet region and the suspended phase. It could be found that the combination of invasive measurements and PEPT provide valuable information for the design and optimization of fluidized bed reactors with a well-defined injection zone.
EAM Import::2019-03-08

Positron emission particle tracking in fluidized beds with secondary gas injection - Hensler, Timo; Tupy, Martin; Strer, Timo; Pöschel, Thorsten; Wirth, Karl-Ernst (Powder Technology, 2015)
We apply positron emission particle tracking (PEPT) to a gas-solid fluidized bed with injection of a secondary gas through a centrally arranged nozzle and present a method to compute stationary fluid-dynamic characteristics of the system from the trajectories of a test particle. In order to evaluate this non-invasive method we compare the field of density obtained by PEPT with the density obtained by a traditional, well-established and approved, yet invasive, measurement technique to find good agreement. Besides the penetration depth of the jet region and the opening angle of the jet which are inferred from the density field, we use PEPT to measure quantities whose measurement using traditional methods is rather sophisticated, including the residence time of particles in the jet region and the suspended phase, the coefficients of axial and radial dispersion and the material flux across the jet boundaries. We conclude that PEPT is a reliable and at the same time versatile technique to measure stationary fluid-dynamic properties of dynamical particle systems at spatial resolution only limited by the duration of the measurement.
Keywords: Dispersion coefficient; Fluidized bed; Measurement technology; Positron emission particle tracking; Residence time; Secondary gas injection

Solid distribution in fluidized and fixed beds with horizontal high speed gas jets - Köninger, Benedikt; Koegl, Thilo; Hensler, Timo; Arlt, Wolfgang; Wirth, Karl-Ernst (Powder Technology, 2018)
High speed jet penetration in fluidized beds can be used for particle size control or comminution processes. Thus, particle breakage is determined by the kinetic energy of the solids and the frequency of particle-particle impacts inside the flow. Both aspects are influenced by the solid concentration inside the jets and at the boundary. For understanding the fundamental breakage mechanism, the determination of the solid distribution in those complex flows is an important contribution. In order to access the turbulent and delicate multiphase flow, a modern fast X-ray computed tomography unit was used in this work. To obtain quantitative solid concentrations, the measurement system was optimized by means of hardware filtering, exposure time and reconstruction algorithm. These methods allowed the investigation of influencing parameters like jet velocity, fluidization velocity or particle size on the solid distribution in a single jet. With the obtained experimental data, correlations for the axial and radial solid distribution were developed. In addition, the influence of multiple jet injection with a common focal point is presented.
Keywords: Horizontal secondary gas injection; Jet milling; X-ray computed tomography; Solid distribution; Visualization of flow pattern